2015
DOI: 10.1111/jop.12305
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in alcohol and tobacco metabolism genes in head and neck cancer in the Basque Country

Abstract: The identified genotypic variations in alcohol and tobacco metabolizing genes only by themselves do not seem to be responsible for the higher incidence of HNSCC observed in the Basque Country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…We selected 37 SNPs with a minor allele frequency (MAF) > 5% in the HapMap Han Chinese population in Beijing that were previously associated with head and neck cancer [2224] for genotyping. Genomic DNA was extracted from peripheral blood leukocytes using GoldMag ® nanoparticles (GoldMag Ltd. Xi'an, China) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We selected 37 SNPs with a minor allele frequency (MAF) > 5% in the HapMap Han Chinese population in Beijing that were previously associated with head and neck cancer [2224] for genotyping. Genomic DNA was extracted from peripheral blood leukocytes using GoldMag ® nanoparticles (GoldMag Ltd. Xi'an, China) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated the correlation between ALDH2 gene or SOD2 gene polymorphisms and susceptibility to HNSCC [12][13][14][15][16][17]. However, the expression pattern of these two genes in HNSCC patients in terms of the amount of alcohol drinking and tobacco smoking has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identification of SNPs, which serve as genetic susceptibility markers of tumors, has become a recent research interest. According to available evidence, SNPs in biotransformation enzymes (Shukla et al, 2012 ), DNA repair genes (Li et al, 2016 ), apoptotic pathways (Ma et al, 2011 ), alcohol metabolism (Bediaga et al, 2015 ), and immune inflammatory cytokines (Singh et al, 2015 ; Ma and Zhou, 2016 ) could affect the risk of HNC. Furthermore, these SNPs may also play a role in prognostication and may serve as a predictive tool in making treatment decisions for HNC (Zafereo et al, 2009 ; Lundberg et al, 2012 ; Sivadas et al, 2013 ; Zou et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%